Book-tax differences e rating - Barbosa, Josilene da Silva (2019)
The study aims to verify the relationship of different types and levels of Book-Tax Differences (BTD) with rating notes. The sample represents 3,737 observations of publicly traded companies from 54 countries analyzed between 2001 and 2016 through logistic regression. The econometric tests involve the different types of BTD (total, positive, negative, abnormal, normal, permanent and temporary) segregated by quintiles. The analysis was also performed by considering the complete sample, the pre- and post-adoption period of IFRS and the legal system. The results show that BTD has useful informational content to rating agencies in their credit risk assessments. As well as, it demonstrates that high levels of BTD (greater distance between accounting and taxable profit) are negatively affecting the rating, and not a least distance between the two profit measures does not seem to indicate a concern to rating agencies and therefore end up not affecting their assessments. Temporary BTD seems to be relevant to explain the rating after the adoption of IFRS, perhaps due to the to the biggest loopholes that accounting choices can generate regarding result management, which may make it difficult for rating agencies to identify btd's discretionary portion. It is believed that the results have a practical contribution by suggesting that the manipulation of accounting numbers may generate negative consequences for companies, especially that managers need to be aware of the reflections of accounting choices, specifically with regard to accounting values affecting BTD.